The fall of Richard Nixon : a reporter remembers Watergate - Brokaw, Tom (Random House, 2019)
"The last year of the Nixon presidency was filled with power politics, legal jiu-jitsu and high-stakes showdowns, with head-shaking surprises every day. Tom Brokaw, the NBC News White House correspondent during the final year of Watergate, gives us a close-up, personal account of the players, the strategies, and the highs and lows of the scandal that brought down a president. Brokaw writes, 'Even now, almost half a century later, I am astonished by what the country went through, and I wanted to share press stories from the inside looking out -- what it was like to be on call 24/7, the twists and turns, the laughs and tensions during this historic time.'"--